2017
DOI: 10.1080/15222055.2017.1339651
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Guadalupe Bass Swim‐up Fry to Hyperoxia

Abstract: Hatchery-reared fingerling Guadalupe Bass Micropterus treculii are stocked into central Texas rivers to restore threatened populations and combat hybridization with Smallmouth Bass M. dolomieu. Fry survival in hatchery rearing ponds has declined by more than 50% in recent years, and pilot investigations indicated that exposure to high dissolved oxygen (DO) concentrations (>20 mg/L; hyperoxia) during tempering might have contributed to fry mortality. To test this hypothesis, Guadalupe Bass swim-up fry (11 d pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…() suggested that GB fry are sensitive to hypo‐ and hyperoxia soon after swim‐up, so DO must be maintained between 6 and 15 mg/L during acclimation (Matthews et al. ). Maintaining DO within this range throughout GB larval culture would be prudent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…() suggested that GB fry are sensitive to hypo‐ and hyperoxia soon after swim‐up, so DO must be maintained between 6 and 15 mg/L during acclimation (Matthews et al. ). Maintaining DO within this range throughout GB larval culture would be prudent.…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects of GB early life history (spawning season and location, fecundity, some nest and egg characteristics, and behavior) have been partially described by Hurst et al (1975), Boyer et al (1977), Edwards (1980), and Carmichael and Williamson (1986). Other published observations on GB have primarily focused on water quality tolerance (Edwards 1978(Edwards , 1980Tomasso and Carmichael 1986;Sullivan et al 2013;Matthews et al 2017), introgression with SMB (Edwards 1979(Edwards , 1980Whitmore and Butler 1982;Whitmore 1983;Garrett 1988Garrett , 1991Morizot et al 1991;Littrell et al 2007;Bean et al 2013;Bean and Grabowski 2015;Fleming et al 2015), habitat (Hubbs 1957;Edwards 1978Edwards , 1980Farquhar 1995;Perkin et al 2010;Bean and Grabowski 2015), phylogeny (Johnson et al 2001;Bagley et al 2011), and reproductive behavior (Lutz-Carrillo et al 2015). Studies of the GB diet are limited to observations of predominantly juvenile and adult fish (Edwards 1980;Day 1981;Carmichael and Williamson 1986;Farquhar 1995).…”
mentioning
confidence: 98%
See 3 more Smart Citations